Difficulties in Reading Muthala'ah Subject among Second-Semester Students of Al-Amien Islamic University - Athifah Saifurrahman; Nursyamsih Nursyamsih (Institut Dirosat Islamiyah Al-Amien Prenduan, 2023)
This study aimed to identify the difficulties faced by female students of the second level in reading recitation, which was conducted in two study centers: 1. What are the difficulties that female students in the second level for girls at Al-Ameen Islamic University of Brandwan found in reading recitation? 2. How to overcome the difficulties encountered by female students in the second level for girls at Al-Ameen Islamic University of Brandon in reading reading? This research is based on describing the two types of method. As for data collection techniques in this study, interviews, notes and documents used in data extraction.